Move Abroad to Move Forward? Self-Assessments of Chinese Students and Undocumented Migrants in France - Florence Lévy; Yong Li (Social Inclusion, 2021)
Migrants’ self-assessments refer to their perceptions of social mobility and positioning. These assessments are often ambivalent and counterintuitive for observers. To overcome contradictory first impressions, we propose a comprehensive approach to migrants’ self-assessments that goes beyond the opposition between objective and subjective social mobility and links the transnational context, various social spheres, actors’ migratory projects, and their reflexivity. The empirical materials in this article draw on two studies on Chinese migrants in France and confront the trajectories and viewpoints of undocumented migrants and international students. Beyond the differences between their experiences and their legal, economic, and social statuses in France and China, we highlight several common points: First, both groups considered migration a lever to improve their social status. Second, their evaluations link their regions of origin and destination as well as various social spheres. Third, in a transnational context, many factors at different scales influence migrants’ subjective self-assessments of the success or failure of their migration. The migrants’ assessments can vary according to their emphasis on professional, personal, or family trajectories, or on their choice of reference groups. They are shaped by the complexity of translations of status from one country to another and by rapid social transformation in China. Thus, many interviewees estimate that they are simultaneously in situations of social progression and regression.